The age-productivity pattern: Do location and sector affiliation matter? - Bernhard Mahlberg; Inga Freund; Jesús Crespo Cuaresma; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2013)
Current demographic developments are expected to challenge the sustainability of welfare in industrialised economies. Persistent low fertility levels and increasing survival rates to older age imply a decreasing share of younger individuals within the labour force that needs to support an increasing share of old people out of the labour force. We use matched employeremployee data for Austria at the firm level in order to study the link between the age structure and labour productivity and concentrate on the role played by regional location and sector affiliation. We apply multilevel estimation techniques in order to account for systematic variation of the age-productivity pattern with regard to these two dimensions. Our results indicate that the age-productivity pattern differs significantly across regions and across sectors and that sectoral differences are the more sizable source of heterogeneity in the link between the age structure and firm productivity.
Keywords: C21; J14; J24; J82; R11; 330; age-productivity profile; firm heterogeneity; employer-employee data; multilevel regression methods; regional variability; sectoral variability; Alternde Bevölkerung; Gesamtwirtschaftliche Produktion; Altersstruktur der Bevölkerung; Arbeitsproduktivität; Österreich